14. Factor x4 + 3x2 - 28.(x2 - 7)(x - 2)(x + 2)(x2 - 2)(x2 + 14)(x2 + 7)(x - 2)(x + 2)(x2 + 4)(x2 - 7)
![14 Factor x4 3x2 28x2 7x 2x 2x2 2x2 14x2 7x 2x 2x2 4x2 7 class=](https://us-static.z-dn.net/files/d87/6a38179b45eb673f9d1021ba470cbc29.png)
Answer:
[tex]x^4+3x^2-28=(x^2+7)(x-2)(x+2)[/tex]Step-by-step explanation:
To factorize the expression, we can use a variable substitution. Let's say that z=x^2.
[tex]\begin{gathered} x^4+3x^2-28 \\ z^2+3z-28 \end{gathered}[/tex]Then, to factorize this we need to factor in the form:
[tex](z+\text{?)(z}+\text{?)}[/tex]The numbers that go in the blanks, have to:
*Add together to get 3
[tex]-4+7=3[/tex]*Multiply together to get -28
[tex]-4\cdot7=-28[/tex]So, we get:
[tex]z^2+3z-28=(z-4)(z+7)[/tex]Substitute the equation z=x^2
[tex](x^2-4)(x^2+7)[/tex]Factorizing the perfect square binomial:
[tex]x^4+3x^2-28=(x^2+7)(x-2)(x+2)[/tex]